The law of private investment funds - Spangler, Timothy (Oxford University Press, 2008)
Provides lawyers with a practical analysis of the legal and regulatory issues that arise from the structure and marketing of private investment funds both from the UK and US perspective. Against the backdrop of regulation and investor protection, this book also offers a discussion of the regulatory and fiduciary duties of fund managers